TECHNICAL ANALYSIS AND BUSINESS FEASIBILITY OF WAVE FISHING GEAR IN THE INSULAR VILLAGE OF THE HIGH WESTERN CLIFFS OF THE MERANTI ISLANDS OF RIAU PROVINCE - Pribadi, Tri Suci; Brown, Arthur; Rengi, Pareng (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in July-August 2018 in the village of Insit, Tebing Tinggi Barat District, Meranti Islands, Riau Province. The objectives of this research are (1) to know the technical analysis of the operation of wave fishing gear, (2) to find out the feasibility of a wave fishery business. The method used in this study is a direct survey method by making observations to the field by looking at fishing activities using wave fishing devices. Data collection was carried out by going directly to the field by making arrests and interviewing the fishermen on the wave.Gombang capture technology influenced several factors that is tidal factor, current velocity, water depth and weather. The results of the business feasibility analysis calculations indicate that fisheries gombang provide benefits to fishermen and deserves to be developed because of the value of BCR (Benefit Cost Ratio) is obtained at 1.8, FRR (Financial Rate of Return) is 34%. and PPC (Payback Period of Capital) is 2 years and 9 month and 15 days. Keywords :Gombang, Technology, Business Feasibility, Desa Insit